Initial results of intraluminal ultrasound in gynecologic diagnosis - Sohn, Christof; Wallwiener, Diethelm; Rimbach, Stefan; Bastert, Gunther (The journal of the American Association of Gynecologic Laparoscopists, 1995)
The interior of hollow organs can be examined using extremely small intraluminal ultrasound transducers inserted into catheters. We tested the practicality of this method and the range of indications for which it could be useful in gynecology by performing initial examinations of extirpated uteri and fallopian tubes. In vivo, we inserted an intraluminal unit with transducer diameters of 3.5F and 5F through the cervix into the fallopian tubes of 15 patients during hysteroscopy or laparoscopy. The catheter was inserted successfully into the tube in all 15 women, and in 9 all the way to the distal end. The tubal wall was identified precisely, and a functional diagnosis of tubal motility was established for the first time. However, it was impossible to differentiate between tubal epithelium and muscularis. Also, uterine endometrium cannot be evaluated accurately with the current level of technology. This technique will enable the first functional examination and diagnosis of the tubes and uterus, provided that further improvements can be made in the quality of the images.